2009
DOI: 10.2337/dc08-2322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Diet Higher in Carbohydrate/Lower in Fat Versus Lower in Carbohydrate/Higher in Monounsaturated Fat on Postmeal Triglyceride Concentrations and Other Cardiovascular Risk Factors in Type 1 Diabetes

Abstract: OBJECTIVETo compare the effects of a eucaloric diet higher in carbohydrate/lower in fat versus lower in carbohydrate/higher in monounsaturated fat on postmeal triglyceride (TG) concentrations and other cardiovascular disease risk factors in nonobese subjects with type 1 diabetes and in good glycemic control.RESEARCH DESIGN AND METHODSIn a parallel group design study, 30 subjects were randomly assigned and completed one of the two eucaloric diets. Assessments included: BMI, blood pressure, A1C, plasma lipids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 14 publications
1
35
0
5
Order By: Relevance
“…More importantly, in some of these studies, test meal composition was according to diet composition, and the LFHC meal had less (14,20), or no (65) fat compared with the HFMUFA meal; therefore, this effect was expected, since meal total fat amount is the main determinant of PPL (14,20,65). However, other studies found benefits of a HFMUFA vs. a LFHC diet, even if the test meal was according to diet composition and therefore of greater fat (24,33,68,79).…”
Section: Amount and Type Of Fatmentioning
confidence: 86%
See 1 more Smart Citation
“…More importantly, in some of these studies, test meal composition was according to diet composition, and the LFHC meal had less (14,20), or no (65) fat compared with the HFMUFA meal; therefore, this effect was expected, since meal total fat amount is the main determinant of PPL (14,20,65). However, other studies found benefits of a HFMUFA vs. a LFHC diet, even if the test meal was according to diet composition and therefore of greater fat (24,33,68,79).…”
Section: Amount and Type Of Fatmentioning
confidence: 86%
“…Several studies have compared the effects on PPL of a diet high in total fat and MUFA (HFMUFA) (olive oil) vs. low in fat and high in carbohydrates (LFHC) and/or vs. a diet high in fat and SFA (HFSFA) (butter). Many (21,24,33,34,39,46,68,69,76,79,90), but not all (4,14,20,26,65,70,71,85), found that the HFMUFA diet was superior to the other two diets in several aspects of postprandial TAG metabolism in both healthy and nonhealthy volunteers (Tables 1 and 2).…”
Section: Amount and Type Of Fatmentioning
confidence: 99%
“…These conclusions are based on posthoc analyses and a cross-sectional study respectively and should therefore be interpreted carefully. Also the conclusion of Strychar et al (Strychar I et al 2009) to recommend a diet higher in MUFA and lower in carbohydrate for nonobese type 1 diabetic individuals to reduce CVD risk factors is doubtful. Their conclusion is based on PAI-1 and VLDL levels, which are not such a good predictors for atherosclerosis (and by extension CVD) as TG levels are.…”
Section: Fatmentioning
confidence: 99%
“…In one trial (Strychar I et al 2009), the authors concluded that a diet lower in carbohydrate and higher in MUFA might be preferable to a diet higher in carbohydrate and lower in MUFA for type 1 diabetic patients. This was solely based on the positive effect on triglyceride (TG) levels and plasminogen activator inhibitor 1 levels (PAI-1) in the first diet.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation